1981
DOI: 10.1093/clinchem/27.5.714
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and intermethod relationships of materials containing purified human pancreatic and salivary amylase.

Abstract: We describe the preparation and characterization of materials containing human pancreatic and salivary alpha-amylase (EC 3.2.1.1) and examine their relationship to endogenous amylase in human serum. Amylase was purified from human pancreas and saliva by solvent- and salt-fractionation and column chromatography to specific activities of 63 and 279 kU/g, respectively. Four liquid pools, differing only in activity, were prepared from each source of amylase, each in a matrix containing, per liter: 30 g of human al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1984
1984
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…According to the data, the average values of Km and Vmax of α-AMY were 0.714 mM and 0.047 mM/min, respectively. The inhibitors were no effect on Km, while Vmax in presence of 75 μg/ml of each of the extracts was decreased to 0.023, and 0.012 mmol min -l , respectively (25) .…”
Section: Kinetic Parameters Of α-Amymentioning
confidence: 83%
See 1 more Smart Citation
“…According to the data, the average values of Km and Vmax of α-AMY were 0.714 mM and 0.047 mM/min, respectively. The inhibitors were no effect on Km, while Vmax in presence of 75 μg/ml of each of the extracts was decreased to 0.023, and 0.012 mmol min -l , respectively (25) .…”
Section: Kinetic Parameters Of α-Amymentioning
confidence: 83%
“…Wasan and Firas, revealed that the specific activity of α-AMY enzyme purified from the blood of diabetic patients was 21.8 U/mg and the degree of purification reached 16.1 with an enzymatic outcome of 108.2% using Ion exchange chromatography and Sephadex G-100 gel filtration column chromatography (24) . From the human pancreas and saliva, α-AMY was purified using solvent and salt fractionation and column chromatography to achieve specific activities of 63 and 279 kU/g, respectively (25) . -----------------------------------------------------------------------------------------------------------------------------------Determination of α-AMY molecular weight By using gel filtration chromatography, the mol.wt.…”
Section: α-Amy Purificationmentioning
confidence: 99%
“…3 Human salivary amylase (α1, 4 α-D glucan, 4 gluconohydrolase) was first described by Leuchs in the year 1831. 4 Human salivary amylase is a major component of human salivary secretions, responsible for hydrolysis of starch into small sugar molecules.…”
Section: Introductionmentioning
confidence: 99%